The factor that influences selection of Islamic banking among Non-Muslim in Melaka / Nur Atika Saad - Saad, Nur Atika (2011)
The emergence of strong Islamic movements in last three decades has generated a renewed interest in Islamic economics, especially in Islamic interest free banking. Currently Islamic bank strategically offering high quality products and services to satisfy their customers due to the strong competition, customer expectation for high quality services and rapidly changes of technology. The purpose of this study is to investigate major factors that are reflecting to customers’ selection toward Islamic banking. This study hopes to analyze and determine the customer selection, quality of product and services, availability of services, confidence in bank and knowledge about Islamic banking system. The analysis confirms the significant positive relationship of quality of services, availability of services, confident of bank and knowledge of Islamic banking social with customers’ selection toward Islamic bank. These factors are expected to have great role for influencing customer mind. In conclusion, customers can derive a better understanding of the activities that are undertaken by bank and how the way these activities are being deal with.